External Communication Strategy Of An Organization: Theoretical Basis And Practical Significance - Nazirov, Xusanjon (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
This article explores the external communication strategy of organizations, its theoretical foundations, and practical significance. It presents the main principles of external communication strategies, the necessary principles for their successful implementation, and various models and methods that bring benefits to organizations. The role of mass media (OAV), public relations (PR), branding, and digital communication is also analyzed. Furthermore, the importance of external communication strategy during crisis situations and the development of new technologies and communication tools are discussed. The article includes both theoretical foundations and real practical examples.